Jurassic palynoevents in the circum-Arctic region - Bujak, Jonathan; Bringué, Manuel; Goryacheva, Anna A.; Lebedeva, Natalia K.; Pestchevitskaya, Ekaterina B.; Riding, James B.; Smelror, Morten (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2022)
Successions of Jurassic strata located in the Arctic region normally yield rich assemblages of terrestriallyderived and marine palynomorphs, reflecting relatively warm air and sea-surface temperatures. The land plant floras were prone to the development of local communities and regional provincialism, whereas the marine biotas thrived across extensive open marine areas with high productivity, resulting in the rapid evolution of dinoflagellate cysts (dinocysts) following their earliest fossil record in the Triassic. Dinocysts exhibit low taxonomic richness and provide low biostratigraphic resolution throughout the Lower Jurassic sections. By contrast, they are diverse in Middle and Upper Jurassic strata where they provide excellent biostratigraphic markers for correlating and dating both surface and subsurface sections. Over twenty formal and informal biozonations based on the firstand last occurrences of dinocysts have been erected in Alaska, Arctic Canada, the Barents Sea region, Greenland and northern Russia, many of which are correlated with macrofossils, including ammonites, that occur in the same sections. This paper presents a compilation of 214 Jurassic palynostratigraphic events (118 first occurrences and 96 last occurrences) that have regional chronostratigraphic value in the Circum-Arctic, based on their published records. Each event is correlated with the base of a chronostratigraphical unit (including formal stages and sub-Boreal ammonite zones), or as an estimated percentage above the base of the chronostratigraphical unit relative to the entire unit. The relationships of each event to stages and key fossil zonal schemes is shown on chronostratigraphic plots using the 2020 version of TimeScale Creator®.